Ethnoecological perspectives on environmental stewardship: Tenets and basis of reciprocity in Gitxsan and nłeʔkepmx (Nlaka'pamux) Territories - Chelsey Geralda Armstrong; Jennifer Grenz; Jennifer Zyp‐Loring; Jade LaFontaine; Leslie Main Johnson; Nancy J. Turner (People and Nature)
Abstract Local and Indigenous Peoples steward and protect a significant proportion of biologically diverse ecosystems globally. This fact is increasingly acknowledged by researchers and international organizations, offering both opportunities and challenges at the intersection of Indigenous and western knowledge production in the context of environmental management research and policy. Drawing on half a century of ethnoecological research and personal experiences in Gitxsan and nłeʔkepmx Territories in the Pacific Northwest of North America, this research considers the role of reciprocity as an inherent philosophy and tenet for successful environmental stewardship. Reciprocity is a legal responsibility and moral perspective that foregrounds many Indigenous worldviews. Such cultural drivers and obligations towards lands and biota appear to be unknown, marginalized or instrumentalized in mainstream and western science and policy. We conclude that fundamental elements of reciprocity may not be adequately blended or braided into western environmental management frameworks. As such, alternatives to blending include acknowledging sole proprietary and self‐determining rights for Indigenous Peoples to govern and steward lands outside of western infrastructures and value systems. This study raises critical questions about the feasibility of reconciling reciprocity with western environmental management practices and regulations. It explores the implications for Indigenous rights and sovereignty, and climate change mitigation. By addressing these complex issues, we contribute to ongoing discourse on the integration of Indigenous and western knowledge in environmental stewardship research, and the ethical, historical and cultural challenges that come with it. Read the free Plain Language Summary for this article on the Journal blog.